2010
DOI: 10.1007/s12031-010-9424-z
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Effects of PACAP on Pancreatic Islets: A Mini-Review

Abstract: Progressive beta-cell insufficiency in the pancreas is a hallmark of both types I and II diabetes, and agents that protect against beta-cell dysfunction are potential drug targets for diabetes mellitus. Pituitary adenylate cyclase-activating polypeptide (PACAP) is a strong secretagogue of insulin from pancreatic islets and is suggested to be involved in physiological blood glucose homeostasis and the pathology of diabetes. Recent studies in genetically engineered animal models have shown that PACAP stimulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
(39 reference statements)
1
18
1
Order By: Relevance
“…Recent data demonstrated that it located in pancreatic islets as well and could potentiate GSIS as an effective insulinotropin in an autocrine and/or paracrine manner (Filipsson et al, 1997;Sakurai et al, 2011). Further studies found that PACAP could be synthesized by islets and stored in the secretory granules of both beta cells and alpha cells (Nakata and Yada, 2007).…”
Section: Silent Information Regulator 2 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data demonstrated that it located in pancreatic islets as well and could potentiate GSIS as an effective insulinotropin in an autocrine and/or paracrine manner (Filipsson et al, 1997;Sakurai et al, 2011). Further studies found that PACAP could be synthesized by islets and stored in the secretory granules of both beta cells and alpha cells (Nakata and Yada, 2007).…”
Section: Silent Information Regulator 2 Proteinmentioning
confidence: 99%
“…Further studies found that PACAP could be synthesized by islets and stored in the secretory granules of both beta cells and alpha cells (Nakata and Yada, 2007). The insulinotropic action involved the binding of PACAP to its specific receptors and the successive coupling to both cyclic AMP and Ca 2 + signaling, the pathways known to be employed also by other incretin hormones, such as GLP-1 (Nakata and Yada, 2007;Sakurai et al, 2011). In addition, transgenic mice with beta-cellspecific overexpression of PACAP were resistant to streptozotocin-induced beta-cell destruction, suggesting the protective effect of PACAP for islet beta cells (Yamamoto et al, 2003).…”
Section: Silent Information Regulator 2 Proteinmentioning
confidence: 99%
“…This approach successfully filters out highly expressed genes in contaminating cell types (e.g., SST, GCG from somatostatin, and glucagon cells contaminating the beta cell population), otherwise mistaken as key players in the expression signature of beta cells. In addition to known beta-cell-specific transcripts (INS, IGF2, PDX1) we highlight further targets, some featured already in a microarray analysis of sorted islet cells (Dorrell et al 2011b), e.g., RGS16, negative regulator of G-protein signaling, involved in endocrine pancreas development and re-expressed in adult cells in response to GLP-1 (Villasenor et al 2010); ADCYAP1, pituitary adenylate cyclase activating polypeptide 1, involved in insulin secretion and beta cell regeneration/proliferation (Sakurai et al 2011); HADH, hydroxyacyl-CoA dehydrogenase, negative regulator of insulin secretion (Hardy et al 2007) associated with Alzheimer's (Nicolls et al 2003), which is in turn associated with diabetes. Many other genes however have not been described before in the context of beta cells, including: NPTX2, neuronal pentraxin 2, found in neuronal cells and gliomas but also shown to be frequently downregulated in pancreatic cancers (Zhang et al 2012); TSPAN1, tetraspanin 1, which can associate with alpha6.beta1 integrin and promote FAK phosphorylation (Huang et al 2008) shown by us to be involved in insulin secretion (Rondas et al 2011); GPM6A, neuronal membrane glycoprotein of unknown function but identified as a beta cell marker in sorted mouse islet cells (Dorrell et al 2011a); BMP5, bone morphogenic protein 5, implicated in pancreas and fetal beta cell development ( Jiang et al 2002); and P2RY1, purinergic receptor through which ADP and ATP modulate insulin secretion (Fernandez-Alvarez et al 2001).…”
Section: à7mentioning
confidence: 99%
“…Thus, PACAP derivatives as VPAC2-specific agonists can effectively promote glucose-dependent insulin secretion, control circulating glucose and protect islet beta cells without causing glucagon secretion and glycogenolysis, and have been proposed as potential T2D therapeutics. [12][13][14] BAY55-9837 is a reported specific VPAC2 agonist constructed through site-directed mutagenesis, and it can increase plasma insulin levels in a dose-dependent manner, but not leading to any hypoglycemia in rats. 15,16 Nevertheless, its therapeutic application has been hampered by its short half-life (~5 min) and limited bioavailability in vivo.…”
Section: Introductionmentioning
confidence: 99%